Disseminated Tuberculosis with Myocardial Involvement: A Rare Case Entity - Alva, Sameeksha; Samartha, Vinitha; Hegde, Shreya (Annals of Pathology and Laboratory Medicine, 2022)
A disease like tuberculosis, which is quite common in India, there is still a delay in diagnosing cardiac involvement by tuberculosis. Here we reported an autopsy case report of a middle-aged man who presented with sudden death. On histopathological examination we found that the deceased is involved of myocardium by Tuberculosis along with lungs. It is important to diagnose the condition earlier to treat the patient accordingly.